Towards a comprehensive understanding of design sketch - a literature review of design sketch taxonomy and considerations for future research / Min Hua ... [et. al] - Hua, Min; Han, Ji; Wang, Pan; Huang, Shan (Universiti Teknologi MARA, Perak, 2018)
Taxonomy is an important approach to characterize the roles of the sketch in design. Design researchers have made various attempts to classify design sketches. However, despite the extensive literature on the subject, the roles that sketch play in design are still not fully understood, especially those changing ones in today’s design context due to the development of CAD/ sketching software. This study performed a literature review of the design sketch taxonomies published over the last thirty years. The objective is to understand the major drawbacks that limit their effective implementation in the research of design sketch. This study developed a Generic Design Process model and proposed criteria for accessing design sketch taxonomies. This study has found that to achieve a comprehensive understanding of design sketch, many taxonomies have limitations in describing the whole design process and revealing the sub-functions of design sketch, which feature a lack of both integrity and accuracy. In addition, most of the taxonomies overlook the importance of non-working sketch, which is also an obstacle for its implementation in the field.